Temperature Sensors: Robust and Stable Ratiometric Temperature Sensor Based on Zn–In–S Quantum Dots with Intrinsic Dual‐Dopant Ion Emissions (Adv. Funct. Mater. 40/2016). (25th October 2016) - Cao, Sheng; Zheng, Jinju; Zhao, Jialong; Yang, Zuobao; Shang, Minghui; Li, Chengming; Yang, Weiyou; Fang, Xiaosheng
Abstract : A robust and stable ratiometric temperature sensor based on Zn‐In‐S quantum dots (QDs) with intrinsic dual‐dopant ion emissions is reported by W.Y. Yang, X.S. Fang, and co‐workers on page 7224. The environment‐friendly co‐doped QD sensor exhibits an excellent stability with almost no hysteresis in cycles. The device is promising for challenging applications in future optical nanothermometry.